The Effectiveness of Functional Analytical Therapy on Controlling, Expressing and Internalizing Anger in Patients with a Borderline Personality Disorder - Siroos , Mandana; Mirzaian , Bahram; Hasanzadeh , Ramazan (Shahroud Journal of Medical Sciences, 2021)
Introduction: Borderline personality disorder affects many cognitive, behavioral, and even emotional domains of individuals. This study aimed to evaluate the effectiveness of functional analytical therapy on controlling, expressing, and internalizing anger in patients with a borderline personality disorder.Methods: The research method was a quasi-experimental pre-test-post-test with experimental and control groups. The statistical population of this study included all 43 women referred to Asal Psychological Clinic in Karaj city in 2020. Out of 33 patients with moderate borderline personality disorder, 24 were selected by simple random sampling method and were randomly assigned to two groups of 12 (experimental and control groups). The functional analytical psychotherapy package of Tsai, Kohlenberg, Kanter & Waltz (2010) was performed on the experimental group in 10 sessions of 45 minutes. For experimental and control groups in pre-test and post-test Anger Questionnaire of Spielberg (1988) was used. Data were analyzed using analysis of covariance mixed with SPSS18 software.Results: The results showed that functional analytical therapy has a significant effect on improving controlling, expressing, and internalizing anger in patients with borderline personality disorder (Pvalue≤0.001).Conclusions: These results emphasize the level of performance of functional analytical psychotherapy in different areas of cognitive, behavioral, and emotional in the treatment of people with a borderline personality disorder.Keywords: Functional therapy, Anger, Borderline personality disorder.